Optical and probe diagnostics of plasma-liquid systems with secondary discharge - Prysiazhnevych, I.V.; Chernyak, V.Ya.; Safonov, E.K. (Вопросы атомной науки и техники, 2007)
A low-pressure plasma-liquid system with secondary discharge was investigated by optical and probes techniques. Emission spectra at the different cross-sections of plasma-liquid reactor were analyzed and the electronic excitation temperature was determined. The voltage jump near the plasma-liquid boundary was observed and possibility of varying of its value by changing the voltage on the secondary discharge was shown.